Teaching Practice for Ideological and Political Education of College English based on Production-Oriented Approach - Li, Chi (Transactions on Social Science, Education and Humanities Research, 2024)
“Ideological and Political Education” is the focus of the reform of college English courses in the new era. This article uses Production-Oriented Approach (POA) as the theoretical basis to design classes and takes the College English course as a case to study how to integrate ideological and political elements into the “motivating, enabling and assessing” teaching procedures. It aims to achieve the organic integration of language learning and ideological education, which provides reference for ideological and political education in college English teaching.